Legal Implications of Changing Commercial Identity Through Naming Rights Agreements - Muhammad Nur Alamsyah; Moh. Sigit Gunawan (Jurnal Legisci, 2026)
Background. The development of naming rights practices in Indonesia shows an increasingly significant shift in commercial identity in modern business activities. However, these developments have not been matched by specific, comprehensive legal arrangements. Aims. This study aims to analyze the legal arrangements related to naming rights agreements and their implications for legal certainty and the parties' protection. Methods. The research method used is normative legal research, employing a statutory and conceptual approach. Result. The results of the study show that naming rights agreements are formally valid under the principle of freedom of contract as stipulated in Article 1338 of the Civil Code, but there remains a substantial legal vacuum in their regulation. Conclusion. In addition, notaries, as public officials, face the risk of legal liability if the deed they prepare does not take into account legal protection and trademark law provisions. Therefore, a special regulation is needed to govern the practice of naming rights in Indonesia to ensure optimal legal certainty and protection. Implication. This void raises various legal implications, including legal uncertainty, inadequate protection for brand owners and sponsors, and potential losses for third-party consumers.